1993
DOI: 10.1016/0014-5793(93)81451-5
|View full text |Cite
|
Sign up to set email alerts
|

Wound‐induced systemic accumulation of a transcript coding for a Bowman‐Birk trypsin inhibitor‐related protein in maize (Zea mays L.) seedlings

Abstract: The wound‐induced accumulation of a transcript coding for a polypeptide of 72 amino acid residues in maize (Zea mays L.) seedlings was investigated. Sequence comparison showed strong homology with Bowman‐Birk trypsin inhibitors of cereal and legume species. The local accumulation pattern of this transcript demonstrated, after wounding various parts of the seedling, a local as well as a systemic response which implies the transmission of a wound signal specifically from the lower to the upper parts of the plant. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…This protein is homologous to ribosome-inactivating proteins (W. Becker and K. Apel, personal communication) and may thus play a fundamental role in translational regulation. A better understanding of wound signalling in monocots is likely to emerge from work on wound-inducible Bowman-Birk trypsin inhibitor in maize seedlings [19]. In this system a wound signal is transmitted unidirectionally (upwards) to tissues distal to the wound site making this an attractive model for systemic signalling.…”
Section: Jasmonates As Wound Signalsmentioning
confidence: 99%
“…This protein is homologous to ribosome-inactivating proteins (W. Becker and K. Apel, personal communication) and may thus play a fundamental role in translational regulation. A better understanding of wound signalling in monocots is likely to emerge from work on wound-inducible Bowman-Birk trypsin inhibitor in maize seedlings [19]. In this system a wound signal is transmitted unidirectionally (upwards) to tissues distal to the wound site making this an attractive model for systemic signalling.…”
Section: Jasmonates As Wound Signalsmentioning
confidence: 99%
“…Wounding of the lower leaves of severa1 plant species results in the accumulation of defense proteins in wounded leaves and in unwounded leaves throughout the plants (Green and Ryan, 1972;Brown et al, 1985;Bradshaw et al, 1989;Eckelkamp et al, 1993;Cordero et al, 1994). Recent studies have provided evidence To whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…However, bsil which appeared to be related to BB-PIs was highly homologous to an aluminium-induced wheat gene, wali5a [45], and exhibited homology to a wound-induced protein, WIP1, from maize [11,41]. This suggested that bsil may be activated by wound damage rather than by a pathogen-derived elicitor.…”
Section: Discussionmentioning
confidence: 87%